Dynamic Morse decompositions for semigroups of homeomorphisms and control systems - Braga Barros, C. J.; Souza, J. A.; Reis, R. A. [UNESP] (Springer/plenum Publishers, 2012)
In this paper, we introduce the concept of dynamic Morse decomposition for an action of a semigroup of homeomorphisms. Conley has shown in [5, Sec. 7] that the concepts of Morse decomposition and dynamic Morse decompositions are equivalent for flows in metric spaces. Here, we show that a Morse decomposition for an action of a semigroup of homeomorphisms of a compact topological space is a dynamic Morse decomposition. We also define Morse decompositions and dynamic Morse decompositions for control systems on manifolds. Under certain condition, we show that the concept of dynamic Morse decomposition for control system is equivalent to the concept of Morse decomposition.
Keywords: Morse decompositions; semigroups of homeomorphisms; control systems